The prevalence of periodontitis in an Iraqi population using the 2017 classification - Imran, Nada K; Abdulbaqi, Hayder R; Milward, Mike (Journal of Baghdad College of Dentistry, 2024)
Background: To determine the prevalence and severity of periodontitis in an Iraqi population using the 2017 classification. Methods: Data on the periodontal status of patients were retrospectively collected from healthcare records. The information included demographics, clinical parameters including bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment loss (CAL). Descriptive and inferential statistical analyses were performed using SPSS (version 26, IBM, USA) software. Results: Out of 1578 records, the periodontal health, gingivitis, and periodontitis represented 26.4%, 37.1%, and 36.5%, respectively with males more affected by periodontal disease compared with females. Periodontitis cases were dominated by stage 3 and 4 which combined accounted for 77.3%, followed by stage 2 (21.3%), and stage 1 (1.4%). When looking at disease grade and levels of stability, localized pattern, Grade C, and unstable status were the most prevalent domains. Regression analysis suggested age, BOP, male, and positive family history as predictors for increasing extent and severity of CAL both in periodontal health and disease. Conclusion: The prevalence of periodontal disease (periodontitis, and gingivitis) was almost equally expressed. Severe periodontitis was the most dominant group whilst milder forms of disease were least prevalent. The data indicated that demographic variables and clinical parameters could predict severity of attachment loss.